IMPROVEMENT OF ACCOUNTING AND REPORTING OF FINANCIAL RESULTS BASED ON INTERNATIONAL STANDARDS - Nodira Khasanova , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The modernization of accounting and financial reporting practices is a critical prerequisite for enhancing the transparency, comparability, and reliability of financial information in emerging economies. In Uzbekistan, the gradual convergence of national accounting systems with International Financial Reporting Standards (IFRS) has gained momentum, particularly in light of economic liberalization reforms initiated since 2017. This paper examines the current state of accounting and financial result reporting in Uzbekistan, identifies existing methodological and procedural shortcomings, and proposes a framework for improving these processes in alignment with international best practices. Empirical analysis based on surveys of 120 enterprises and evaluation of sectoral financial reports reveals that inconsistencies in revenue recognition, asset valuation, and disclosure practices remain prevalent, limiting the utility of financial information for stakeholders. The study advocates for the adoption of standardized IFRS-based templates, comprehensive retraining programs for accountants, enhanced regulatory oversight, and digitalization of reporting processes. Predictive modeling suggests that full IFRS adoption could enhance financial transparency indices by 23–26% and increase foreign investment attractiveness by up to 18% within five years. The findings provide actionable insights for policymakers, professional accounting organizations, and enterprises seeking to elevate the credibility and efficiency of Uzbekistan’s financial reporting ecosystem.